Translational Learnings in the Development of Chemo-Immunotherapy Combination to Bypass the Cold Tumor Microenvironment in Pancreatic Ductal Adenocarcinoma - Kaplon, Hélène (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is among the most lethal cancer, with a 5-year relative survival rate of 5%. The desmoplastic stroma found in the tumor microenvironment of PDAC is suggested to be partly responsible to the resistance to most therapeutic strategies. This review outlines the clinical results get with immune checkpoint inhibitor in PDAC and discuss the rationale to use a combination of chemotherapy and immune checkpoint therapy. Moreover, essential parameters to take in account to design an efficient combination have been highlighted.